UMMATAN WASATAN DALAM QS. AL-BAQARAH 2 : 143 STUDI KOMPARATIF TAFSIR AL-MISHBAH, AL-AZHAR DAN AN-NUR - Rifan Syah, Haekal Pratomo (UIN Sumatera Utara Medan, 2023)
This study discusses the wasatan community in QS. Al-Baqarah/2: 143 comparative study of the interpretations of Al-Mishbah, Al-Azhar and An-Nur, with the aim of examining this meaning in the view of M. Quraish Shihab, HAMKA and T. M. Ash-Shiddieqy. In this study the authors found similarities and differences between the three books of interpretation. The equations are as follows: 1). In Tafsir Al-Mishbah, Al-Azhar and An-Nur the word ummatan wasathan is interpreted as a middle class. 2). In the three interpretations it is written that the Prophet Muhammad was a witness for his people and the people of the Prophet Muhammad SAW could be a witness for others if they made the prophet Muhammad an example.Keywords: Ummatan wasatan, Al-Mishbah, Al-Azhar, An-Nur.